Research on the traction dynamic of shearer based on the pose analysis. (December 2021) - Ma, De-jian; Wan, Li-rong; Lu, Zhen-guo; Zhang, Xin; Zeng, Qing-liang; Gao, Kui-dong
Highlights: A dynamic model of the traction is established considering the shearer's swing. The x-axis swing of the shearer increases the support load of the walking wheel. The y-axis swing intensifies the lateral force unbalance of the guide slipper. The z-axis swing aggravates the wear of the support slipper. The slipper load distribution is improved with the inward contra-rotating. Abstract: The high reliability traction of the shearer is the key to realize safe and efficient coal mining. However, with the popularity of high-power and high-speed shearer, the drawback of frequent failure of traction unit is increasingly apparent. Therefore, to improve the traction reliability of the shearers, a dynamic model of double traction units of the shearer was established. Based on the pose analysis, the dynamic properties of the traction unit were studied, and the effects of constraint state, traction velocity, coal seam dip, depression mining angle and drum steering were discussed. The results show that the dynamic difference between the two traction units is significant affected by the shearer pose. The x-axis swing of the shearer increases the support load of the walking wheel, the y-axis swing intensifies the unbalance of the lateral force of the guide slipper, and the z-axis swing aggravates the fatigue wear of the right support slipper and the impact wear of the left. The load uniform quality of the guide slipper decreases with the increase of velocity and coal seam dip. And the inward contra-rotating of the drum and appropriately increasing the depression angle can improve the load uniform characteristics of the support slipper. The results provide a reference for improving the traction reliability of the shearer and optimizing mining technology.